2005
DOI: 10.1155/np.2005.245
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Constraint‐Induced Movement Therapy and Forced Use in Children With Hemiplegia

Abstract: Hemiplegia is a physical impairment that can occur in childhood following head hemiplegia. In this review, we provide a brief description of forced use and CI therapy and their historical basis, provide a summary of studies of these interventions in children, and discuss a number of important theoretical considerations, as well as implications for postural control. We will show that whereas the studies to date suggest that both forced use and CI therapy appear to be promising for improving hand function in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 69 publications
5
99
0
4
Order By: Relevance
“…Using the same basic method, more improvements have been demonstrated in young children with CP [20]. Moreover the choice of intervention come in agreement with who stated that CIMT was an effective approach for treating developmental disregard in patients with unilateral motor involvement [21]. In addition to, the present study cope with several systematic reviews and randomized controlled trials (RCTs) had demonstrated that CIMT improved functional performance and ADL in children with CP which came in agreement with the results of the present study that showed significant difference in scores of PMAL-R post training in favor to group (A) reflecting improvement in functional upper limb movement [9,22].…”
Section: Resultssupporting
confidence: 61%
“…Using the same basic method, more improvements have been demonstrated in young children with CP [20]. Moreover the choice of intervention come in agreement with who stated that CIMT was an effective approach for treating developmental disregard in patients with unilateral motor involvement [21]. In addition to, the present study cope with several systematic reviews and randomized controlled trials (RCTs) had demonstrated that CIMT improved functional performance and ADL in children with CP which came in agreement with the results of the present study that showed significant difference in scores of PMAL-R post training in favor to group (A) reflecting improvement in functional upper limb movement [9,22].…”
Section: Resultssupporting
confidence: 61%
“…Paediatric mCIT appears promising but the previously available data relates predominantly to preschool children with congenital hemiparesis, mild spasticity, and at least some residual hand function. 17 The children who took part in the present study were older, with more severe motor impairment, and a mixture of dystonia and spasticity. Despite a chronic, often severe, functional impairment of hand function (no active grasp in half the cases), all participants made functional improvements years after AIS and apparent plateauing of recovery.…”
Section: Discussionmentioning
confidence: 89%
“…Training that focuses on promoting the usage of the affected leg, such as the training method presented in this paper, is called unilateral training or constraint-induced movement therapy [23], [24]. On the other hand, training that realizes coordinated movements between both the legs, such as the one developed in our previous study, is called bilateral training [25].…”
Section: Unilateral and Bilateral Trainingmentioning
confidence: 99%